“Many Boys Escaped from Here”: Atypical Migrations in Artistic-Literary Approaches of Szopienice by Kazimierz Kutz, Henryk Bereska and Hilary Krzysztofiak - Tomczok, Marta (Porównania, 2022)
The article is an attempt to trace the migrant fate of the artists born in Szopienice (a district of Katowice): Kazimierz Kutz, Henryk Bereska and Hilary Krzysztofiak on the basis of their works. Reaching for the concept of atypical migrations, the author analyzes the reasons for the post-war departures of the inhabitants of the Katowice district (family, identity, educational, health) against the broad background of the migration of Silesians after 1945, especially to Germany. In this system, artistic migrations become an extensive reflection on a phenomenon that has so far been rarely studied and scattered, providing material not only to historians of literature or art, but also to sociologists. The analysis consists of a part devoted to the borderland, barren land and the aesthetics of representations of migration. In conclusion, there is a proposal to understand its views beyond autobiography, on several levels, including the collective biography of the inhabitants of the district (Kutz) and supra-individual observations (Bereska), embedding the experience of borders, even after their removal, in the biographies of people of the twentieth and twenty-first centuries.